Long-Term Effects of Social-Emotional Learning on Academic Skills: Evidence from a Randomized Trial of INSIGHTS. Issue 1 (2nd January 2021) - McCormick, Meghan P.; Neuhaus, Robin; O'Connor, Erin E.; White, Hope I.; Horn, E. Parham; Harding, Samantha; Cappella, Elise; McClowry, Sandee
Abstract: Social-Emotional Learning (SEL) programs are school-based preventive interventions that aim to improve children's social-emotional skills and behaviors. Although meta-analytic research has shown that SEL programs implemented in early childhood can improve academic and behavioral outcomes in the short-term, there is limited work examining program effects on children's math and language skills in the longer-term. Moreover, few studies have considered variation in impacts by children's pre-intervention academic skills. Using an experimental design, the current study leveraged administrative data available through school records ( N  = 353) to examine the impacts of one SEL program— INSIGHTS into Children's Temperament —implemented in early elementary school on math and language standardized test scores from third through sixth grade. Findings revealed positive average treatment effects on English/Language Arts (ELA) test scores in third and fourth grade, but not in fifth and sixth grade. Students who had higher academic skills at study enrollment showed lasting impacts on ELA scores in fourth, fifth, and sixth grade. There were no treatment impacts on math skills, and no variation in effects on math achievement by baseline skills. Implications are discussed.